2021
DOI: 10.1002/chem.202104224
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Scope of Polyoxometalates as Artificial Proteases towards Hydrolysis of Insoluble Proteins

Abstract: Despite the enormous importance of insoluble proteins in biological processes, their structural investigation remains a challenging task. The development of artificial enzyme‐like catalysts would greatly facilitate the elucidation of their structure since currently used enzymes in proteomics largely lose activity in the presence of surfactants, which are necessary to solubilize insoluble proteins. In this study, the hydrolysis of a fully insoluble protein by polyoxometalate complexes as artificial proteases in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 71 publications
0
30
0
Order By: Relevance
“…3,41 On the other hand, the presence of Zr−K 2:2 alone in solution results in a lower CMC of 0.06 wt % due to the large number of countercations of the POM, which can contribute to shielding the repulsive interactions between the negatively charged head groups of SDS and thereby facilitate micelle formation. 23,53 The ternary system�containing SDS, Mb, and Zr−K 2:2�gave rise to a CMC of around 0.11 wt %, which lies between the CMC in the presence of the POM alone and the CMC with just Mb. This shows the competing influence of the protein and the POM on the CMC of SDS, but the effect of the POM seems to dominate overall.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,41 On the other hand, the presence of Zr−K 2:2 alone in solution results in a lower CMC of 0.06 wt % due to the large number of countercations of the POM, which can contribute to shielding the repulsive interactions between the negatively charged head groups of SDS and thereby facilitate micelle formation. 23,53 The ternary system�containing SDS, Mb, and Zr−K 2:2�gave rise to a CMC of around 0.11 wt %, which lies between the CMC in the presence of the POM alone and the CMC with just Mb. This shows the competing influence of the protein and the POM on the CMC of SDS, but the effect of the POM seems to dominate overall.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In addition, M-POMs have shown high selectivity toward the hydrolysis of peptide bonds involving amino acids with carboxylate groups in their side chains, such as aspartate (Asp) and glutamate (Glu) residues . Moreover, unlike most natural enzymes, M-POMs preserve their catalytic activity in the presence of surfactants. In fact, it was recently demonstrated by our group that in the presence of surfactants, M-POMs can serve as effective catalysts in the hydrolysis of partially soluble unstructured proteins and even insoluble proteins, which are biologically important but remain understudied. , In general, the use of M-POMs as effective catalysts for the hydrolysis of both soluble and insoluble proteins could impact a wide variety of fields including drug design, disease prediction, biotechnology, medicine, and pharmacology among many others . Moreover, the ability of surfactants to provide structural insights through how they affect a protein combined with the hydrolytic cleavage catalyzed by M-POMs can be used as a powerful tool to extract additional information about the protein’s structure that cannot be obtained otherwise.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Parac-Vogt's group has reported Zr-and Hf-based POMs that successfully catalyse peptide bond scission. 16,17 To overcome peptide misfolding, numerous strategies have been reported to face these challenges like using conformationally restricted peptides 18 or encapsulating them inside nanoparticles. 19 Figure 2.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] More recently, polyoxometalates (POMs), which are defined as a large group of negatively charged metal-oxo clusters formed by early transition metal ions in their highest oxidation state, have shown potential to be developed into artificial proteases. [12][13][14][15][16][17] We have shown that POMs bearing highly Lewis acidic Zr(IV), Ce(IV) and Hf(IV) metal ions hydrolyze a wide range of proteins in an efficient and predictable manner, under mild reaction conditions. [14,18] Interestingly, selectivity and efficiency of protein hydrolysis can be tuned by the addition of surfactants, which induce structural changes in the protein through unfolding of their secondary structures.…”
Section: Introductionmentioning
confidence: 99%
“…[17] The use of surfactants has been further leveraged in the hydrolysis of partially soluble and insoluble proteins such as Zein and β-casein, as their addition increased the solubility of the proteins, allowing them to be targeted by Zr(IV) and Hf(IV) substituted POMs . [16,22] The ability of POMs to maintain hydrolytic activity in the presence of surfactants, under which most of the natural enzymes are deactivated, showcases their potential as artificial proteases for investigating insoluble proteins and highly hydrophobic proteins such as membrane proteins. These proteins are highly underrepresented in proteomics study, as they are unsuitable for digestion in traditional aqueous medium, but are highly important in terms of drug targeting, diseases prediction, pharmacological, and biomedical studies.…”
Section: Introductionmentioning
confidence: 99%